Dinâmica de macroinvertebrados em um lago costeiro do sul do Brasil(Lagoa da Reserva, Mostardas-RS) - Santos, Edison Martins dos (Universidade do Vale do Rio do Sinos, 2008)
In view of its great biological diversity and productivity, in addition to its many functions and values, the wetlands ecosystems are priority for conservation. The lack of information about biodiversity is the main limitation for their conservation. Moreover, the identification of the environmental factors responsible for the structure of biological communities in wetlands still remains as a major challenge to the ecology. This study aimed to: i) the lifting of the diversity of macroinvertebrates of a coastal lake in southern Brazil, and ii) examine the effects of environmental parameters of water (conductivity and concentrations of nitrate and orthophosphate) and the sediment (percentage of organic matter) in wealth, abundance and composition of macroinvertebrates over a year. A total of 1,346 individuals distributed on 30 taxa of macroinvertebrates as found in the Lagoa da Reserva over the period studied. The phylum Arthropoda represented 71percent of taxa sampled in the study. The most representative taxa
Keywords: áreas úmidas; dinâmica; ecossistema aquático; lagoa costeira; planice costeira; Rio Grande do Sul; biologia aquática; macroinvertebrados; dynamics; wetlands; macroinvertebrates; Ciências Biológicas